Prognostic value of rare IKZF1 deletion in childhood B-cell precursor acute lymphoblastic leukemia: an international collaborative study - Boer, J M; van der Veer, A; Rizopoulos, D; Fiocco, M; Sonneveld, E; de Groot-Kruseman, H A; Kuiper, R P; Hoogerbrugge, P; Horstmann, M; Zaliova, M; Palmi, C; Trka, J; et al. (Leukemia, 2016)
Deletions in IKZF1 are found in ~15% of children with B-cell precursor acute lymphoblastic leukemia (BCP-ALL). There is strong evidence for the poor prognosis of IKZF1 deletions affecting exons 4-7 and exons 1-8, but evidence for the remaining 33% of cases harboring other variants of IKZF1 deletions is lacking. In an international multicenter study we analyzed the prognostic value of these rare variants in a case-control design. Each IKZF1-deleted case was matched to three IKZF1 wild-type controls based on cytogenetic subtype, treatment protocol, risk stratification arm, white blood cell count and age. Hazard ratios for the prognostic impact of rare IKZF1 deletions on event-free survival were calculated by matched pair Cox regression. Matched pair analysis for all 134 cases with rare IKZF1 deletions together revealed a poor prognosis (P<0.001) that was evident in each risk stratification arm. Rare variant types with the most unfavorable event-free survival were DEL 2-7 (P=0.03), DEL 2-8 (P=0.002) and DEL-Other (P<0.001). The prognosis of each type of rare variant was equal or worse compared with the well-known major DEL 4-7 and DEL 1-8 IKZF1 deletion variants. We therefore conclude that all variants of rare IKZF1 deletions are associated with an unfavorable prognosis in pediatric BCP-ALL.
Keywords: proporcionální rizikové modely; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Child, Preschool; pre-B-buněčná leukemie; transkripční faktor Ikaros; Adolescent; prognóza; protein PEBP2A2; mezinárodní spolupráce; Child; Infant; Proportional Hazards Models; dítě; Adult; dospělí; fúzní onkogenní proteiny; Gene Deletion; mladiství; předškolní dítě; Core Binding Factor Alpha 2 Subunit; Oncogene Proteins, Fusion; lidé; Humans; kojenec; delece genu; Prognosis; Ikaros Transcription Factor; International Cooperation